2003
DOI: 10.1152/ajpcell.00217.2003
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis by Cd2+ or CdMT in proximal tubule cells: different uptake routes and permissive role of endo/lysosomal CdMT uptake

Abstract: The mechanisms of cadmium-metallothionein (CdMT) uptake and toxicity in proximal tubule (PT) cells are not well understood. The effects of 10 microM CdCl2 or Cd7MT-1 (MT-1 saturated with 10 microM CdCl2) on 109Cd2+ uptake, viability, and MT levels of cultured rat PT cells were investigated. Apical 109Cd2+ uptake was measured in confluent monolayers, apoptosis was assessed with Hoechst 33342, and intracellular MT levels were monitored by immunofluorescence and quantitative morphometry. 109Cd2+ uptake into PTC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
47
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 37 publications
7
47
0
Order By: Relevance
“…The activation of caspases after 24-h exposure to 10 M Cd 2ϩ occurs concomitantly with the observation of cytochrome c release (Fig. 2) and correlates with the kinetics of accumulation of 109 Cd 2ϩ by PT cells (11). We have recently shown that direct application of 2-10 M Cd 2ϩ to isolated kidney cortex mitochondria triggers mitochondrial swelling and the release of cytochrome c (20).…”
Section: A Late Event In CD 2ϩ Apoptosis: Caspase Activationsupporting
confidence: 72%
“…The activation of caspases after 24-h exposure to 10 M Cd 2ϩ occurs concomitantly with the observation of cytochrome c release (Fig. 2) and correlates with the kinetics of accumulation of 109 Cd 2ϩ by PT cells (11). We have recently shown that direct application of 2-10 M Cd 2ϩ to isolated kidney cortex mitochondria triggers mitochondrial swelling and the release of cytochrome c (20).…”
Section: A Late Event In CD 2ϩ Apoptosis: Caspase Activationsupporting
confidence: 72%
“…Here, we demonstrate that 10 M Cd 2ϩ induces apoptosis of rat kidney PT cells at 6 and 24 h whereas Cyt c release is observed after 24 h only, when intracellular Cd 2ϩ concentrations may be high enough to interact directly with mitochondria (16). Cyt c release may be partially mediated by direct effects of Cd 2ϩ on mitochondrial permeability pathways; Cd 2ϩ induces swelling (EC 50 ϳ 9 M) and release of Cyt c from energized mitochondria and mitoplasts isolated from rat kidney cortex.…”
mentioning
confidence: 71%
“…After degradation of GSH by ␥-glutamyltranspeptidase bound to the apical plasma membrane of PT cells (10), Cd 2ϩ may also be taken up as a free ion through yet unknown apical transport pathways. In a cell line derived from the S1 segment of rat PT, we have previously demonstrated that Cd 2ϩ (10 M) is taken up by apical pathways, which operate with slow kinetics and saturate at 24 h (16).…”
mentioning
confidence: 99%
“…Therefore we used the property of MT as a high-affinity Cd 2ϩ -binding protein to further characterize RME via 24p3R. In PT cells, endocytosed Cd 2ϩ 7 -MT is degraded in lysosomes and free Cd 2ϩ transported via DMT-1 into the cytosol, which induces cell death (39,58). Indeed, a similar mechanism was operative in 24p3R-transfected CHO cells and mDCT209 cells and Cd 2ϩ 7 -MT-induced cell death could be prevented by co-incubation with 24p3 (Fig.…”
Section: Discussionmentioning
confidence: 99%